DIGITAL INDIA: WHERE KNOWLEDGE IS STRENGTH AND EMPOWERS THE PEOPLE - Ahmad Dar, Showkat; Nagrath, Dolly (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2022)
The phrase "Digital India" has become India's catchphrase for the 21st century. Digital India is the result of a great number of technology advances and new inventions that have been developed over time. Prime Minister Narendra Modi is credited for being the driving force behind the "Digital India" plan. The ambitious Digital India initiative has been launched by the government of India. This initiative seeks to connect and deliver government programmes and services digitally while also mobilizing the IT capabilities of government departments across the country. The ultimate goal of this initiative is to transform India into an informed economy and a digitally empowered society with good governance for citizens. Without a doubt, the beginning of the digital revolution can be traced back to the first time digitization was implemented. The BJP government in India is responsible for the realization of this dream. As a direct result of this goal, the government has worked to increase internet connectivity as well as online infrastructure in order to make public services available to all people of the country, especially those who live in remote areas. The purpose of the initiative was to support India in its efforts to become a more economically and technologically developed nation. Before it can be properly implemented, there are a number of challenges that need to be conquered first. The purpose of the study is to shed light on the potentials as well as the inadequacies of the digital India programme.